Charlie Hernández & the league of shadows - Calejo, Ryan (Calejo, Ryan. Charlie Hernández., 2019)
Steeped in Hispanic folklore since childhood, middle schooler Charlie Hernândez learns the stories are true when, shortly after his parents disappearance, he grows horns and feathers and finds himself at the heart of a battle to save the world.